IKLIM ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KEDISIPLINAN KERJA PEGAWAI PADA KANTOR SEKRETARIAT DPRD KABUPATEN BIMA - firmansyah kusumayadi; Muhammad Ali (Master of Management, Mataram University, 2019)
This study aims to determine the effect of Organizational Climate and Organizational Commitment to Employee Work discipline at the Bima Regency DPRD Secretariat office. The dependent variable used is Work Discipline, the independent variable is Organizational Climate and Organizational Commitment. This type of research is causal associative. The sampling technique used is the Census technique to obtain a total sample of 48 respondents who are civil servants. Data analysis techniques in this study were multiple linear regression, t-test, f-test, and adjusted determination coefficient test (R2). From the regression results for this study the equation is obtained, namely Y = 8.756 + 0.565 X1 + 0.434 X2. The results of this study indicate that partially the organizational climate has a positive and significant effect on employee work discipline. Partially, organizational commitment has a positive and significant effect on employee work discipline. Simultaneously the organizational climate and organizational commitment have a positive and significant effect on employee work discipline at the Bima Regency DPRD Secretariat office.Keywords: organizational climate, organizational commitment, work discipline